Does work location influence determinants of employee retention? A multi-group study in the construction sector - Ling, Pick-Soon; Nurul Sarah Mohd-Ossman,; Wong, Yie-Sing (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines the determinants of employee retention by comparing construction sector employees in two different work locations, namely, site- and office-based. The questionnaire approach was used to collect data from 269 employees working in the construction sector in Sarawak. The partial least square structural equation modelling (PLS-SEM) and multi-group analysis (PLS-MGA) were utilised to analyse the data. The results showed that all four constructs are positively related to employee retention in the complete sample set. Compensation and work environment factors significantly affected employee retention in construction site-based employees while only compensation was found to have an insignificant negative effect on office-based employee retention. The PLS-MGA further confirmed the significant effect of compensation on employee retention in the construction sector across different work locations. The findings suggest that effective human resource management strategies could be enhanced by designing different policies that target construction sector employees in different work locations.